If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 30) + 6x = 22 Reorder the terms: 2(30 + x) + 6x = 22 (30 * 2 + x * 2) + 6x = 22 (60 + 2x) + 6x = 22 Combine like terms: 2x + 6x = 8x 60 + 8x = 22 Solving 60 + 8x = 22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -60 + 8x = 22 + -60 Combine like terms: 60 + -60 = 0 0 + 8x = 22 + -60 8x = 22 + -60 Combine like terms: 22 + -60 = -38 8x = -38 Divide each side by '8'. x = -4.75 Simplifying x = -4.75
| x^2-10x+15=-10 | | x+4+4x-8+7x-35=180 | | 0.33333333x+-3=3 | | -0.18/t=-5.2 | | 9x+2+13x-18+17x+1=180 | | 12=z/-9 | | 0=10x^4-24x^3-3x^2 | | 3.2x+6=15 | | x/7+5=-2 | | x/18=2 | | Y-1=X-3 | | 4x-3+9x-6+6x-1=180 | | 8(5-x^2)-3= | | z/7+9=5 | | X^4-13x^3+36= | | 6t-.16666667=9 | | 3(X+1)-2(X-2)=5 | | 18/48 | | 2/5-2/10 | | 5x-4+3=9-x | | -39+x^2=10x | | 42-21x+252=44 | | 6x-27=0findx | | 3(x-1)=2(5+x) | | 5x-8+7x-31+63=180 | | (6x^4+6x^3-7)-(8x^2-4x+7)= | | 3(x-2)=4(2-x) | | -4.37*(-5.2)= | | Y=1/2pog4x | | 9(5-2x)+x=-15 | | 2x+3x-4+3-4x=8-3 | | (3z)/(z^2-16) |